2019
DOI: 10.3389/fphys.2019.01008
|View full text |Cite
|
Sign up to set email alerts
|

The Cattle Fever Tick, Rhipicephalus microplus, as a Model for Forward Pharmacology to Elucidate Kinin GPCR Function in the Acari

Abstract: The success of the acaricide amitraz, a ligand of the tick tyramine/octopamine receptor (a G protein-coupled receptor; GPCR), stimulated interest on arthropod-specific GPCRs as targets to control tick populations. This search advances tick physiology because little is known about the pharmacology of tick GPCRs, their endogenous ligands or their physiological functions. Here we explored the tick kinin receptor, a neuropeptide GPCR, and its ligands. Kinins are pleiotropic insect neuropeptides but their function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 68 publications
1
24
0
Order By: Relevance
“…Identification of G proteins are also relevant for the understanding of acari biology in general, as these proteins could be targeted by novel compounds. Most information on acari GPCRs were obtained from tick transcriptome datasets and recombinant receptor systems (Gross et al, 2015; Xiong et al, 2019). Previous experiments in ticks indicated that prediction of GPCRs using transcriptome analysis might be a challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of G proteins are also relevant for the understanding of acari biology in general, as these proteins could be targeted by novel compounds. Most information on acari GPCRs were obtained from tick transcriptome datasets and recombinant receptor systems (Gross et al, 2015; Xiong et al, 2019). Previous experiments in ticks indicated that prediction of GPCRs using transcriptome analysis might be a challenging task.…”
Section: Discussionmentioning
confidence: 99%
“…To help visualize the sequence conservation of tick kinins across species in relation to the herein determined potency of the Rhimi kinins, the kinin peptide precursor sequences of seven hard tick species were aligned. 39 Sequences were aligned with MegaPro (DNASTAR, Lasergene v16.0) using the MAFFT 43 program with the iterative refinement algorithm E-INS-I because of the occurrence of known insertions and deletions during the evolution of neuropeptide genes. 39 The kinin conserved motifs are represented by Logos obtained with the default alignment settings of MegaPro.…”
Section: Multiple Sequence Alignmentmentioning
confidence: 99%
“…30 To fill this gap in knowledge for the tick KR, we cloned the cDNA of the kinin neuropeptide precursor from R. microplus. Within the translated amino acid sequence, we predicted the sequences of 17 tick kinins, based on both the identification of the canonical conserved residues in the pentapeptide kinin core 'FXXWGa' (FXXWGG) and the putative dibasic enzyme cleavage cutting sites (KK/KR/RR) on the precursor, 38,39 but their activity on the receptor has not yet been tested. The current study determined the activities of the predicted R. microplus endogenous kinin ligands and modified analogs on the recombinant tick KR through a cellular functional assay using calcium fluorescence as a reporter and in high-throughput mode.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations